2017
DOI: 10.1128/jcm.01954-16
|View full text |Cite
|
Sign up to set email alerts
|

Field Validation of SYBR Green- and TaqMan-Based Real-Time PCR Using Biopsy and Swab Samples To Diagnose American Tegumentary Leishmaniasis in an Area Where Leishmania (Viannia) braziliensis Is Endemic

Abstract: The precise diagnosis of American tegumentary leishmaniasis (ATL) is an essential task due to the disease's associated morbidity. A noninvasive, extremely sensitive, and highly specific exam is critical, particularly for mucosal leishmaniasis (ML), in which a low parasite quantity is expected. We aimed to compare the diagnostic accuracy of swab and biopsy sample analysis using SYBR Green-and TaqManbased real-time PCR (qPCR) assays with that of a composite reference standard consisting of the Montenegro skin te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 37 publications
2
46
1
Order By: Relevance
“…However, quantitative PCR (qPCR) does not directly measure the number of viable parasites circulating in the blood, but rather the amount of circulating parasite DNA. Therefore, sensitivity of qPCR depends on assay design (primer and target region), chemistry used (SYBER Green or TaqMan), nature of clinical samples (blood, skin, bone marrow or splenic fluids) and the DNA extraction methods (manual vs commercial kits) [126] (Table-2). Using this technique, it was earlier demonstrated that the simultaneous quantitative evaluation of Leishmania DNA and cytokine by Real Time PCR assay allows prediction of the development of disease in asymptomatic infected dogs [127].…”
Section: Standard Diagnostic Tools and Their Limitationsmentioning
confidence: 99%
“…However, quantitative PCR (qPCR) does not directly measure the number of viable parasites circulating in the blood, but rather the amount of circulating parasite DNA. Therefore, sensitivity of qPCR depends on assay design (primer and target region), chemistry used (SYBER Green or TaqMan), nature of clinical samples (blood, skin, bone marrow or splenic fluids) and the DNA extraction methods (manual vs commercial kits) [126] (Table-2). Using this technique, it was earlier demonstrated that the simultaneous quantitative evaluation of Leishmania DNA and cytokine by Real Time PCR assay allows prediction of the development of disease in asymptomatic infected dogs [127].…”
Section: Standard Diagnostic Tools and Their Limitationsmentioning
confidence: 99%
“…1,2 Real-time PCR (qPCR) is considered a very efficient technique, and it adds quantitative results to clinical analyses. [3][4][5] We aimed to test the accuracy of the combination of a Novy-MacNeal-Nicolle (NNN) medium culture and TaqManbased qPCR analysis for the diagnosis of TL. Sample size was calculated 6 considering a 70% prevalence of ATL in this population 5,7 with a null hypothesis for sensitivity set at 70%, an alternative hypothesis for sensitivity set at 90%, power set at ≥80% and the P-value set to be <0.05.…”
mentioning
confidence: 99%
“…Case and control definition was performed according to a composite reference standard as described elsewhere. 4 For the index test, the preparation of the culture media was adapted according to the methodology described by Romero et al 8 Culture material was withdrawn from a lesion edge aspirate 8 (Fig. 2).…”
mentioning
confidence: 99%
See 2 more Smart Citations